A kind of highly dispersed nano composite carbon black and preparation method thereof
By performing liquid phase recombination and vacuum drying on carbon black, the small molecule decomposition problems caused by easy agglomeration of carbon black particles and high-temperature drying are solved, and the high dispersion and modification performance are improved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202310671473.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-06-07
AI Technical Summary
Carbon black particles are prone to agglomeration and poor dispersion. High-temperature drying can easily lead to small molecules decomposition, affecting the modification performance, and may lead to contamination of drying equipment.
The bifunctional modified substance is used to recombine the carbon black in liquid phase and dried in sections under vacuum to avoid high temperature decomposition and equipment contamination.
The dispersion and purity of carbon black are improved, the modification performance is ensured, and efficient and continuous industrial production is achieved.
Smart Images

Figure CN116904042B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon black, and in particular to a highly dispersed nano composite carbon black and a preparation method thereof. Background Art
[0002] Carbon black is a nanostructured functional filler that is widely used in rubber, plastic, coatings and other industries. However, due to the large specific surface area of carbon black particles and their easy agglomeration, it is difficult to achieve uniform dispersion of carbon black in a polymer matrix or organic solvent, improve the dispersibility of carbon black in a polymer matrix or organic solvent and the compatibility between the dispersion media, and give carbon black high added value.
[0003] In order to improve the dispersion performance of carbon black in polymer matrix, the commonly used modification method is mainly surface grafting modification. In the prior art, organic compounds and carbon black are usually mixed and in-situ grafting modification is performed by heating, ultrasound, mechanical shearing, supercritical and other methods. The subsequent products need to be dried at high temperature to obtain finished products. In industrial production, in order to ensure continuous production, high-temperature drying is usually used to achieve the purpose of rapid evaporation of water and increase production. However, for some small molecular substances with high heat sensitivity, high temperature will cause the small molecules to decompose and affect their modified performance. In addition, the decomposed substances are easy to corrode the drying equipment and cause metal impurity pollution. Problems such as the performance requirements of the modified carbon black cannot be guaranteed.
[0004] Therefore, how to provide a carbon black modification method that can simultaneously improve the dispersibility and purity of carbon black is an urgent problem that needs to be solved by those skilled in the art. Summary of the invention
[0005] In view of this, the present invention provides a method for preparing highly dispersed nano-composite carbon black to solve the problems that carbon black particles are easy to agglomerate and have poor dispersibility, and high-temperature drying easily leads to decomposition of small molecules and affects the modified performance.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A method for preparing highly dispersed nanocomposite carbon black comprises the following steps:
[0008] (1) crushing and dissolving carbon black, adding a modified substance, and stirring to obtain a composite slurry;
[0009] (2) Drying the composite slurry in sections under vacuum conditions to obtain composite carbon black.
[0010] Preferably, in the above method for preparing highly dispersed nano-composite carbon black, the modified substance is a compound containing two or more functional groups.
[0011] Preferably, in the above-mentioned method for preparing highly dispersed nano-composite carbon black, the modified substance includes any one or more of methylamine, stearic acid, sodium dodecylbenzene sulfonate, ethylenediamine, diisopropylamine, triethanolamine, dialkyl phosphite, polyethylene glycol-p-isooctylphenyl ether, methyltrimethoxysilane, hexamethyldisilane, and triethoxysilane.
[0012] Preferably, in the above-mentioned method for preparing highly dispersed nanocomposite carbon black, the carbon black pulverizing and dissolving comprises: shearing and pulverizing the carbon black and dissolving it in water to obtain a carbon black slurry;
[0013] The mass percentage of carbon black in the carbon black slurry is 2-50%.
[0014] Preferably, in the above method for preparing highly dispersed nanocomposite carbon black, the modified substance accounts for 0.5-5% of the total solids;
[0015] and / or the stirring rate is 200-5000 rpm, and the stirring time is 30-300 min;
[0016] And / or the viscosity of the composite slurry is ≤10000cps.
[0017] Preferably, in the above method for preparing highly dispersed nano-composite carbon black, the vacuum degree of the vacuum pumping condition is 0.083-0.095 MPa.
[0018] Preferably, in the above-mentioned method for preparing highly dispersed nano-composite carbon black, the staged drying is sequentially drying at 140-180°C, 80-140°C, and 50-80°C, and when the moisture content of the material is less than 2%, the composite carbon black is discharged.
[0019] Preferably, in the above-mentioned method for preparing highly dispersed nanocomposite carbon black, step (1) is carried out in a pulping device, and step (2) is carried out in a vacuum drying device, and the pulping device is connected to the vacuum drying device through a vacuum pipeline;
[0020] Further preferably, the vacuum drying device includes a drying furnace, which is sequentially provided with a high temperature section, a medium temperature section and a low temperature section, and the high temperature section, the medium temperature section and the low temperature section are all provided with an electric heating system and a temperature control system, and the temperature control system controls the electric heating system to heat according to a preset temperature.
[0021] Preferably, in the above method for preparing highly dispersed nano-composite carbon black, the composite slurry is sprayed into the drying furnace in the form of a spray, and the atomization frequency is 5-30 Hz.
[0022] On the other hand, the present invention also provides a highly dispersed nano-composite carbon black prepared by any of the above methods.
[0023] The present invention provides a highly dispersed nanocomposite carbon black and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention adopts a bifunctional modified substance, and carries out liquid phase compounding with carbon black to make the modified substance uniformly dispersed in the carbon black, thereby ensuring the uniformity of carbon black modification. The carbon black is coated and modified by liquid phase compounding to achieve uniform mixing at the molecular and atomic levels, and the reaction is easily controlled and other components are conveniently added.
[0025] The present invention adopts a specific vacuum drying device to spray the composite slurry into the vacuum drying device for segmented drying, which can avoid the high-temperature decomposition of the modified substance affecting its modified performance, and solve the problem of metal impurity pollution caused by the decomposed substance easily corroding the drying equipment;
[0026] The present invention is based on a feeding and discharging linkage mechanism integrating liquid phase compound and vacuum drying, which can not only ensure high quality and high efficiency of material drying but also ensure the continuity of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0028] Figure 1 It is a schematic diagram of a preparation device for highly dispersed nano-composite carbon black of the present invention.
[0029] In the figure:
[0030] 100 - pulping cylinder, 110 - top cover, 111 - observation port, 200 - stirring device, 210 - stirring blade, 220 - shear blade, 300 - vacuum pipe, 400 - drying furnace, 410 - electric heating system, 420 - temperature control system, 500 - sealing system, 600 - sprayer, 700 - vacuum pump, 800 - dust filter, 900 - online moisture meter. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The embodiment of the present invention provides a method for preparing highly dispersed nano-composite carbon black, comprising the following steps:
[0033] Step S100. The carbon black is sheared, crushed and dissolved in water to obtain a carbon black slurry.
[0034] This step is carried out in a pulping device, which includes a pulping cylinder 100 and a stirring device 200; a top cover 110 is provided on the top of the pulping cylinder 100, and a feeding port for feeding materials and an observation port 111 for observing the mixing state of the materials are provided on the top cover 110, and an end cover is provided on the feeding port, and the end cover is locked after the feeding is completed to ensure the stability of the pressure of the entire system; the stirring device 200 includes a stirring blade 210 and a shearing blade 220 arranged inside the pulping cylinder 100, and at least three stirring blades 210 are provided for stirring the materials, and the shearing blade 220 is located at the bottom of the stirring blade 210 and close to the top of the pulping cylinder 100, and is used to crush the carbon black raw material; the stirring device 200 uses a servo motor to adjust the stirring rate of the motor through a speed regulating device, and the stirring blade 210 and the shearing blade 220 can operate separately or simultaneously.
[0035] Specifically, the carbon black to be modified is placed in the pulping cylinder 100, a proper amount of water is added, the stirring device 200 is turned on, and the carbon black is sheared and crushed by the shear blade 220 to prepare a uniformly dispersed carbon black slurry.
[0036] In some embodiments of the present invention, the stirring rate of the stirring device 200 is set to 300-30000rpm, preferably 1000-20000rpm, more preferably 3000-10000rpm, for example, it can be 3000rpm, 5000rpm, 8000rpm, 10000rpm, etc.; the mass ratio of carbon black raw material in carbon black slurry is 2-50%, preferably 5-45%, more preferably 10-40%, further preferably 15-30%, for example, it can be 15%, 20%, 25%, 30%, etc.
[0037] Step S200. Add a modified substance to the carbon black slurry and stir to obtain a composite slurry.
[0038] This step is also carried out in the pulping device, where the modified substance is added to the carbon black slurry, and the modified substance and the carbon black slurry are evenly mixed by the stirring blade 210, so that the modified substance is evenly dispersed on the surface of the carbon black, and the top cover 110 of the pulping cylinder 100 is closed.
[0039] In some embodiments of the present invention, the mass of the modified substance accounts for 0.5-5% of the total solid mass, preferably 1-5%, more preferably 3-5%, for example, it can be 3%, 4%, 5%; the stirring rate of the stirring blade 210 is set to 200-5000rpm, preferably 500-3000rpm, more preferably 1000-2000rpm; the stirring time is set to 30-300min, preferably 50-200min, more preferably 50-100min, for example, it can be 50min, 80min, 100min, etc.; and the viscosity of the composite slurry is tested, which is required to be no higher than 10000cps.
[0040] Further, the modified substance is a compound containing two or more functional groups, and the modified substance includes but is not limited to any one or more of methylamine, stearic acid, sodium dodecylbenzene sulfonate, ethylenediamine, diisopropylamine, triethanolamine, dialkyl phosphite, polyethylene glycol p-isooctylphenyl ether, methyltrimethoxysilane, hexamethyldisilane, and triethoxysilane. It is understandable that the modified substance can be adjusted according to actual conditions, and the selection is not limited to the substances listed above.
[0041] Step S300: Dry the composite slurry in sections under vacuum conditions to obtain composite carbon black.
[0042] This step is carried out in a vacuum drying device, and the pulping device is connected to the vacuum drying device through a vacuum pipe 300; the vacuum drying device includes a drying furnace 400, and the drying furnace 400 is sequentially provided with a high temperature section, a medium temperature section and a low temperature section, and the high temperature section, the medium temperature section and the low temperature section are all provided with an electric heating system 410 and a temperature control system 420, and the temperature control system 420 controls the electric heating system 410 to heat according to a preset temperature; wherein the high temperature section controls the temperature range of 0-180°C, the medium temperature section controls the temperature range of 0-140°C, and the low temperature section controls the temperature range of 0-80°C.
[0043] Furthermore, the vacuum drying device also includes a sealing system 500 for sealing the drying furnace 400 to effectively ensure the vacuum degree of the furnace body; an online moisture meter 900 is provided at the rear end of the drying furnace 400 to test the moisture content of the material near the discharge port of the drying furnace 400.
[0044] In some embodiments of the present invention, the vacuum degree of the vacuum pumping condition is 0.083-0.095MPa. By adjusting the internal pressure of the furnace body, the vacuum degree in the drying furnace 400 is stabilized, thereby reducing the boiling point of the liquid in the carbon black slurry, and achieving a better drying effect. For heat-sensitive materials that are not suitable for high-temperature drying, the drying time can be effectively shortened, and the product drying efficiency can be improved. It should be noted that the vacuum pump 700 evacuates the drying furnace 400 through a pressure control system, so that the pressure in the drying furnace 400 is always maintained at a set value, and a dust removal filter 800 is provided at the input end of the vacuum pump 700 to prevent the dust extracted from the drying furnace 400 from entering the vacuum pump 700.
[0045] Furthermore, the staged drying is carried out in sequence through a high temperature section of 140-180°C, a medium temperature section of 80-140°C, and a low temperature section of 50-80°C, and when it is detected that the material is dried to a moisture content of less than 2%, it is discharged to obtain composite carbon black.
[0046] Furthermore, the composite slurry is sprayed into the drying furnace 400 in the form of a spray. The inlet of the drying furnace 400 is provided with a sprayer 600, and its atomization frequency is 5-30 Hz, preferably 10-20 Hz, for example, 10 Hz, 15 Hz, 20 Hz, etc.
[0047] In other embodiments of the present invention, a highly dispersed nano-composite carbon black prepared by the above method is also provided. Since the highly dispersed nano-composite carbon black is prepared by the above method, the highly dispersed nano-composite carbon black in this embodiment has all the advantages mentioned in the above preparation method, and no further description is given. In general, the dispersion performance of the highly dispersed nano-composite carbon black is effectively improved.
[0048] Example 1
[0049] Put 500g of carbon black into the slurry cylinder, add 5000ml of water at the same time, close the top cover, turn on the stirring device, use the shear blade to shear and crush the carbon black, set the speed to 10000rpm, crush for 30min, open the top cover and add 15g of hexamethyldisilane for low-speed stirring, the stirring rate is 3000r / min, the stirring time is 180min, and the viscosity of the composite slurry is tested to be 1000cps;
[0050] Close the top cover of the cylinder, turn on the electric heating system of the drying furnace, set the temperature of the high temperature section to 150℃, the medium temperature section to 120℃, and the low temperature end to 70℃, heat according to the set temperature, evacuate the drying furnace body, set the vacuum degree to 0.09Mpa, set the atomization frequency to 15Hz, spray the composite slurry into the drying furnace, set the speed of the drying furnace to 10r / min, and use the vacuum pump to evacuate the drying furnace through the pressure control system to keep the furnace pressure at the set value of 0.09Mpa. Test the water content of the material with an online moisture meter. When the water content is lower than 2%, open the discharge port to allow the material to rotate and be discharged into the finished product tank in sequence.
[0051] Example 2
[0052] (1) 1000g of carbon black was placed in a slurry cylinder, and 12000ml of water was added at the same time. The top cover was closed, and the stirring device was turned on. The carbon black was sheared and crushed using a shear blade. The speed was set to 8000rpm and the crushing was performed for 90min. The top cover was opened and 15g of ethylenediamine was added for low-speed stirring. The stirring rate was 2000r / min and the stirring time was 200min. The viscosity of the composite slurry was tested to be 3000cps.
[0053] Close the top cover of the cylinder, turn on the electric heating system of the drying furnace, set the temperature of the high temperature section to 170℃, the medium temperature section to 100℃, and the low temperature end to 70℃, heat according to the set temperature, evacuate the drying furnace body, set the vacuum degree to 0.094Mpa, set the atomization frequency to 18Hz, spray the composite slurry into the drying furnace, set the speed of the drying furnace to 5r / min, and use the vacuum pump to evacuate the drying furnace through the pressure control system to keep the furnace pressure at the set value of 0.094Mpa. Test the water content of the material with an online moisture meter. When the water content is lower than 2%, open the discharge port to allow the material to rotate and be discharged into the finished product tank in sequence.
[0054] Example 3
[0055] Put 200g of carbon black into the slurry cylinder, add 10000ml of water at the same time, close the top cover, turn on the stirring device, use the shear blade to shear and crush the carbon black, set the speed to 300rpm, crush for 60min, open the top cover and add 1g of dialkyl phosphite for low-speed stirring, the stirring rate is 200r / min, the stirring time is 300min, and the viscosity of the composite slurry is tested to be 2000cps;
[0056] Close the top cover of the cylinder, turn on the electric heating system of the drying furnace, set the temperature of the high temperature section to 140℃, the medium temperature section to 80℃, and the low temperature end to 50℃, heat according to the set temperature, evacuate the drying furnace body, set the vacuum degree to 0.083Mpa, set the atomization frequency to 5Hz, spray the composite slurry into the drying furnace, set the speed of the drying furnace to 10r / min, and use the vacuum pump to evacuate the drying furnace through the pressure control system to keep the furnace pressure at the set value of 0.083Mpa. Test the water content of the material with an online moisture meter. When the water content is lower than 2%, open the discharge port to allow the material to rotate and be discharged into the finished product tank in sequence.
[0057] Example 4
[0058] Put 5000g of carbon black into the slurry cylinder, add 10000ml of water at the same time, close the top cover, turn on the stirring device, use the shear blade to shear and crush the carbon black, set the speed to 30000rpm, crush for 10min, open the top cover and add 250g of methyltrimethoxysilane for low-speed stirring, the stirring rate is 5000r / min, the stirring time is 30min, and the viscosity of the composite slurry is tested to be 6000cps;
[0059] Close the top cover of the cylinder, turn on the electric heating system of the drying furnace, set the temperature of the high temperature section to 180℃, the medium temperature section to 140℃, and the low temperature end to 80℃, heat according to the set temperature, evacuate the drying furnace body, set the vacuum degree to 0.095Mpa, set the atomization frequency to 30Hz, spray the composite slurry into the drying furnace, set the speed of the drying furnace to 12r / min, and evacuate the drying furnace through the pressure control system to keep the furnace pressure at the set value of 0.095Mpa. Test the water content of the material with an online moisture meter. Open the discharge port when the water content is lower than 2%, and let the material rotate and discharge into the finished product tank in sequence.
[0060] Three samples of the composite carbon black prepared in Examples 1 to 4 were taken for grafting rate test to evaluate the modification uniformity. The results are shown in Table 1. The grafting rate is calculated as follows:
[0061] Grafting rate W = (Wa-Wb) / Wb×100%
[0062] Wa is the ratio of the residual mass of carbon black to the initial mass of carbon black at 500 °C;
[0063] Wb is the ratio of the residual mass of the modified carbon black at 500 °C to the initial mass of the modified carbon black.
[0064] Table 1
[0065]
[0066] As can be seen from Table 1, the ratio of the actual average grafting rate to the theoretical grafting rate using the method of the present invention is above 93%, and the absolute difference between samples is no more than 1% of the average value, indicating that the surface of the modified composite carbon black is evenly grafted.
[0067] Comparative Example 1
[0068] Comparative Example 1 is basically the same as Example 1, with the only difference being that 50 g of carbon black is put into a pulping drum and 5000 ml of water is added at the same time.
[0069] Comparative Example 2
[0070] Comparative Example 2 is substantially the same as Example 1, with the only difference being that 2600 g of carbon black is placed in a pulping drum and 5000 ml of water is added at the same time.
[0071] Comparative Example 3
[0072] Comparative Example 3 is substantially the same as Example 1, except that 30 g of hexamethyldisilane was added and stirred at a low speed.
[0073] Comparative Example 4
[0074] Comparative Example 4 is substantially the same as Example 1, except that 2 g of hexamethyldisilane is added and stirred at a low speed.
[0075] Three samples of the composite carbon black prepared in Comparative Examples 1-4 were taken for grafting rate test to evaluate the modification uniformity. The results are shown in Table 2.
[0076] Table 2
[0077]
[0078] It can be seen from Comparative Examples 1-2 in Table 2 that in the method of the present invention, as the amount of carbon black increases, the ratio of the average value of the actual grafting rate to the theoretical grafting rate can be maintained above 90%, and the absolute difference between the samples is no more than 1% of the average value. However, as the proportion of carbon black gradually increases, the ratio of the average value of the actual grafting rate to the theoretical grafting rate tends to decrease and approaches 90%. Therefore, the amount of carbon black added is limited to 2-50% of the carbon black slurry.
[0079] It can be seen from Comparative Examples 3-4 that in the method of the present invention, as the amount of modified substance added changes, the ratio of the actual average grafting rate to the theoretical grafting rate can be maintained above 90%, and the absolute difference between samples is no more than 1% of its average value. However, as the proportion of modified substances gradually increases, the ratio of the actual average grafting rate to the theoretical grafting rate tends to decrease and approaches 90%. Therefore, the amount of modified substance added is limited to 0.5-5% of the total solid amount.
[0080] Therefore, it can be shown from Examples 1-4 and Comparative Examples 1-4 that in the nano-composite carbon black prepared by the method of the present invention, the loss of modified substances is small, the grafting rate is high, and the surface modification uniformity of the carbon black is high.
[0081] Comparative Example 5
[0082] Comparative Example 5 is substantially the same as Example 1, except that the drying furnace is not vacuumed and is operated under normal pressure.
[0083] Comparative Example 6
[0084] Comparative Example 6 is substantially the same as Example 1, with the only difference being that the high temperature section is set at 130°C, the medium temperature section is set at 75°C, and the low temperature end is set at 45°C.
[0085] Comparative Example 7
[0086] Comparative Example 7 is substantially the same as Example 1, the only difference being that the high temperature section is set at 180°C, the medium temperature section is set at 150°C, and the low temperature end is set at 90°C.
[0087] Comparative Example 8
[0088] Comparative Example 8 is substantially the same as Example 1, except that no staged drying is performed and the drying is performed at 120° C. until the water content is less than 2%.
[0089] Three samples of the composite carbon black prepared in Comparative Examples 5-8 were taken for grafting rate test to evaluate the modification uniformity. The results are shown in Table 3.
[0090] Table 3
[0091]
[0092] As can be seen from Table 3, by comparison, it is found that the actual grafting rate and product uniformity of the composite carbon black prepared without vacuum in Comparative Example 5 are significantly reduced, indicating that the modified substance is decomposed in a non-vacuum drying environment, and continuous vacuum conditions need to be ensured in the drying furnace of the present invention; it can be found from Comparative Examples 6-8 that the drying temperature in Comparative Example 6 is reduced, which to a certain extent prolongs the time of the material in the drying cylinder, and relatively increases the time the material stays in the medium and high temperature stage, thereby causing partial decomposition of the modified substance and reducing the grafting rate to a certain extent; the drying temperature in Comparative Example 7 is increased, which accelerates the decomposition of heat-sensitive substances at high temperatures and exceeds their decomposition temperature, thereby reducing the grafting rate and affecting the uniformity; in Comparative Example 8, no segmented drying is performed, which to a certain extent prolongs the time the material stays in the drying cylinder, and relatively increases the time the material stays in this temperature stage, thereby causing partial decomposition of the modified substance, reducing the grafting rate to a certain extent and affecting the uniformity.
[0093] In summary, the present invention uses a small molecular weight, bifunctional organic small molecule to graft one end of the molecule to the surface of carbon black, fill it into a polymer that is incompatible with the other end, and utilize the agglomeration effect of the ungrafted end to form a nano carbon black particle chain in the polymer matrix, thereby improving the dispersibility of carbon black.
[0094] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the scheme disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0095] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing highly dispersed nanocomposite carbon black, characterized in that: The following steps are involved: (1) After the carbon black is crushed and dissolved, the modified substance is added and stirred to obtain a composite slurry; (2) drying the composite slurry in stages under vacuum conditions to obtain composite carbon black; The modified substance includes any one or more of methylamine, stearic acid, sodium dodecylbenzene sulfonate, ethylenediamine, diisopropylamine, triethanolamine, dialkyl phosphite, polyethylene glycol p-isooctylphenyl ether, methyltrimethoxysilane, hexamethyldisilane, and triethoxysilane; The carbon black crushing and dissolving comprises: shearing and crushing the carbon black and dissolving it in water to obtain a carbon black slurry; the mass percentage of the carbon black in the carbon black slurry is 2-50%; The modified substance accounts for 0.5-5% of the total solid content; and / or the stirring rate is 200-5000 rpm, and the stirring time is 30-300 min; and / or the viscosity of the composite slurry is ≤10000 cps; The vacuum degree of the vacuum pumping condition is 0.083-0.095MPa; The stepwise drying is carried out in sequence at 140-180° C., 80-140° C., and 50-80° C., and when the moisture content of the material is less than 2%, the composite carbon black is discharged.
2. The method for preparing highly dispersed nanocomposite carbon black according to claim 1, characterized in that: Step (1) is carried out in a pulping device, and step (2) is carried out in a vacuum drying device, wherein the pulping device is connected to the vacuum drying device via a vacuum pipeline; The vacuum drying device includes a drying furnace, which is sequentially provided with a high temperature section, a medium temperature section and a low temperature section, and the high temperature section, the medium temperature section and the low temperature section are all provided with an electric heating system and a temperature control system, and the temperature control system controls the electric heating system to heat according to a preset temperature.
3. The method for preparing highly dispersed nanocomposite carbon black according to claim 2, characterized in that: The composite slurry is sprayed into the drying furnace in the form of a spray, and the atomization frequency is 5-30 Hz.
4. A highly dispersed nanocomposite carbon black prepared by the method according to any one of claims 1 to 3.
Citation Information
Patent Citations
Multifunctional vacuum drying oven and stage drying process thereof
CN103123208A
Modification treatment method of waste tire pyrolysis carbon black
CN111500092A
Pyrolysis carbon black deep processing modification method and equipment applied to method
CN111690273A
Preparation method of nano carbon black
CN114181547A
Carbon black nano material with high filtering precision and preparation method thereof
CN114574002A